2006
DOI: 10.1126/science.1121422
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of the Lantibiotic Cyclase Involved in Nisin Biosynthesis

Abstract: Nisin is a posttranslationally modified antimicrobial peptide that is widely used as a food preservative. It contains five cyclic thioethers of varying sizes that are installed by a single enzyme, NisC. Reported here are the in vitro reconstitution of the cyclization process and the x-ray crystal structure of the NisC enzyme. The structure reveals similarities in fold and substrate activation with mammalian farnesyl transferases, suggesting that human homologs of NisC posttranslationally modify a cysteine of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
384
0
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 281 publications
(409 citation statements)
references
References 31 publications
11
384
0
14
Order By: Relevance
“…LanCs have about 400 amino acid residues, and possess a double α-barrel-fold topology (17) and a strictly conserved Cys-Cys-His triad near their C termini for binding of a zinc ion. In vitro reconstitution of the nisin cyclase activity of NisC and solution of its crystal structure have supported a zincdependent mechanism (17,18). The zinc ion is believed to activate the Cys thiols of the precursor peptide for nucleophilic attack on the dehydroamino acids.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…LanCs have about 400 amino acid residues, and possess a double α-barrel-fold topology (17) and a strictly conserved Cys-Cys-His triad near their C termini for binding of a zinc ion. In vitro reconstitution of the nisin cyclase activity of NisC and solution of its crystal structure have supported a zincdependent mechanism (17,18). The zinc ion is believed to activate the Cys thiols of the precursor peptide for nucleophilic attack on the dehydroamino acids.…”
Section: Resultsmentioning
confidence: 93%
“…This system is a prime example of the highly evolvable nature of ribosomal biosynthesis to access high structural diversity of natural products at low genetic cost. Analysis of the ProcM sequence revealed that this enzyme contains a "CCG" motif (30) rather than a "CHG" motif (17,18) found in all LanCs and most of the LanMs known to date, indicating that ProcM likely uses three Cys residues rather than a Cys-Cys-His triad for binding of the active site zinc ion. Model studies of activation of thiolate nucleophiles by Zn 2+ have demonstrated increased reactivity with an increased number of thiolate ligands (33), suggesting that ProcM may derive its promiscuity in part from a highly active zinc ion (30).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of various RiPP biosynthetic enzymes have provided several examples of biocatalysts that can generate a macrocyclic product from a linear peptide substrate (14,28,30,31,(52)(53)(54). Such enzymes represent a next-generation technological utility, but many of these catalysts are often slow or require sequence constraints on substrates.…”
Section: Discussionmentioning
confidence: 99%
“…LanC enzymes are zinc metalloproteins in which the bound metal ion activates the thiol moiety of the cysteine residue for nucleophilic addition onto dehydrated S (Dha) and T (Dhb) residues. Consistent with this, PspC contains the conserved H and C residues that coordinate the zinc ion in NisC (44). Thus, PspC is proposed to be the cyclase responsible for (Me)Lan bridge formation in planosporicin.…”
Section: Identification Of P Alba As a Planosporicin Producer Fourmentioning
confidence: 60%